2011
DOI: 10.1073/pnas.1117773108
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes isocitrate dehydrogenase-dependent carboxylation of α-ketoglutarate to citrate to support cell growth and viability

Abstract: Citrate is a critical metabolite required to support both mitochondrial bioenergetics and cytosolic macromolecular synthesis. When cells proliferate under normoxic conditions, glucose provides the acetyl-CoA that condenses with oxaloacetate to support citrate production. Tricarboxylic acid (TCA) cycle anaplerosis is maintained primarily by glutamine. Here we report that some hypoxic cells are able to maintain cell proliferation despite a profound reduction in glucose-dependent citrate production. In these hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
801
8
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 876 publications
(873 citation statements)
references
References 25 publications
(38 reference statements)
38
801
8
3
Order By: Relevance
“…For instance, recent findings showed an unknown role of glutamine in a panel of human tumor cell lines with defective mitochondria or under a hypoxia condition. In particular, these cell lines produce citrate by reductively carboxylating α-KG via NADPH-dependent isocitrate dehydrogenase (IDH), supporting lipogenesis [37,38]. In agreement with this study, some somatic mutations in the IDH-1 and IDH-2 genes have been found in gliomas and acute myelogenous leukemia (AML).…”
Section: Glutamine Metabolismsupporting
confidence: 81%
“…For instance, recent findings showed an unknown role of glutamine in a panel of human tumor cell lines with defective mitochondria or under a hypoxia condition. In particular, these cell lines produce citrate by reductively carboxylating α-KG via NADPH-dependent isocitrate dehydrogenase (IDH), supporting lipogenesis [37,38]. In agreement with this study, some somatic mutations in the IDH-1 and IDH-2 genes have been found in gliomas and acute myelogenous leukemia (AML).…”
Section: Glutamine Metabolismsupporting
confidence: 81%
“…1a) including an increased NADH/NAD + ratio 18,22 , an increased intracellular concentration of αKG 18,23 , and acidification of the extracellular and intracellular environments 24,25 . Prior reports implicated lactate dehydrogenase A (LDH) and malate dehydrogenase 1 and 2 (MDH) as contributing to hypoxia-induced L-2HG in cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a) 18,2325 , but it is unclear to what extent these conditions might be sufficient to induce production of L-2HG. Therefore, we tested the effects of acidified medium and/or exogenous αKG on cells cultured in normoxia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both IDH1 and 2 have potential roles in hypoxia‐induced reductive carboxylation,29, 31 suggesting that this pathway may be perturbed in IDH1‐mutated gliomas. Given that the cytosolic pathway has been shown to be important in hypoxic reductive carboxylation for lipogenesis,30, 32, 33, 34 and that gliomas appear to ‘favor’ IDH1 mutations, there may be a requirement for IDH2 wild‐type activity in hypoxic IDH1 mutant gliomas. However, a recent paper also showed that IDH1 ‐mutated cells retained more of their oxidative TCA cycle metabolism than their wild‐type counterparts 117.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%